ANALISIS TINGKAT KEPUASAN PENGUNJUNG ATAS KUALITAS PELAYANAN MINIMARKET BARU BUMIAYU - Aprilia, Nur Wulan; Lubis, Nawazirul; Nurseto, Sendhang (Jurnal Ilmu Administrasi Bisnis, 2013)
Developments and competition in the retail business or minimarket increasingly sharp. Each minimarket promising satisfaction. Since the creation of satisfaction will benefit the company. Based on this formulation of the problem in research is still the detection of these complaints as an indication of dissatisfaction with the performance of services visitors BARU minimarket Bumiayu. This study aims to determine the level of compatibility between visitors' expectations and the performance of the services provided and to determine the level of visitor satisfaction BARU minimarket Bumiayu the quality of services provided by the BARU minimarket Bumiayu. This type of research is descriptive by using primary data. The data was collected using data collection instruments such as guiding question for obtaining data from the company, while to obtain data from 100 respondents using a questionnaire. The sampling technique used is incidental sampling. Furthermore, the data obtained in the field is processed in the form of tabulations that are then analyzed. Data analysis method used is descriptive qualitative. From the calculation of the level of visitor satisfaction, the performance of the minimarket at 3.68 to 4.62 deduced visitors' expectations in general, visitors were satisfied with the performance of services in the BARU minimarket Bumiayu. From the calculation, it can be concluded the level of compatibility between the expectations of visitors and overall implementation performance minimarket at 79.91% can be categorized according to the expected visitors. Although the dimensions of direct evidence such as the condition of air conditioning was considered quite appropriate 64.86%, condition of toilets 57.05% considered less appropriate and assessed the condition of the parking lot does not conform 42.56%. The suggestions can be given in this study include the company can use the types of lights that are brighter that the products look more obvious, improve the toilets and provide clues and symbols toilet, increasing the number of air conditioning to keep the room cooler, maximizing the suggestion box because the company suggestion box can find weaknesses so that they can take appropriate action for the development of the minimarket.